2018
DOI: 10.14419/ijet.v7i2.5.13965
|View full text |Cite
|
Sign up to set email alerts
|

Increase the PSNR Of Image Using LZW and AES Algorithm With MLSB on Steganography

Abstract: There are many research has done a hybridization approach of text message insertion that has been compressed with Lempel-Ziv-Welch (LZW) algorithm and has also been encrypted. The text messages in ciphertext form are inserted into the image file using LSB (Least Significant Bit) method. The results of this study indicate that the value of Peak Signal to Noise Ratio (PSNR) lower than the LSB method of 0.94 times with a ratio of 20.33%, with Kekre's method of 10.04%. To improve the value of PSNR stego image of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Besides, the aforementioned, researchers found that the importance of reinforcing text steganography and cryptography methods lies in protecting the secret keys, which are considered the most critical element in information security technologies [35,37,149]. However, only a few researchers have used an encryption to improve the efficiency of their methods [150,151].…”
Section: Securitymentioning
confidence: 99%
“…Besides, the aforementioned, researchers found that the importance of reinforcing text steganography and cryptography methods lies in protecting the secret keys, which are considered the most critical element in information security technologies [35,37,149]. However, only a few researchers have used an encryption to improve the efficiency of their methods [150,151].…”
Section: Securitymentioning
confidence: 99%